Propagation models for train environment over geo satellite networks in Malaysia - Jasim Al-Jumaily, Abdulmajeed Hammadi (2014)
Recent advances in satellite communication technologies in the tropical regions have led to significant increase in the demand for services and applications that require high channel quality for stationary and mobile satellite terminals. The lack in reliable, accurate analysis and assessment for the stationary and mobile scenarios regarding the attenuation due to rain and power arch supply PAs. These is a need to determine and quantify these risk factors which, in its turn, leads to optimize service quality particularly in Malaysian region. Moreover, the current satellite propagation models are done at temperate regions which exhibit different environmental characteristics than seen in Malaysia. That makes their propagation models inaccurate and irrelevant to the tropical regions in general. The propagation models for the stationary and mobile scenario of high speed train to produce a reliable analysis on the attenuation, due to rain and power arch supply, in tropical region, represents an interesting area to study for propagation impairment in Malaysia. The rainfall characteristics in the tropical region differ significantly from those in temperate regions, the rain effects problem is more crucial for tropical regions such as Malaysia because of their high intensity rainfall. This study presents for stationary scenario (Malaysia-PMSS) an analysis of experimental data compared against six existing rain attenuation prediction models namely, the ITU-R-618-11, ITU-R-618-5, DAH, Crane, Brazil, and SAM models. The data are analyzed in two ways. First, rain attenuation prediction models are statistically analyzed. Second, the measured data and existing prediction model are compared. A communication system design can estimate the exact rain attenuation for three locations Selangor, Penang, and Johor regions of Malaysia and can produce a suitable design for better communication service. Additionally, new method for developing measured data is suggested: the Exponential Moving Average (EMA). Throughout the literature, the location Selangor and elevation angle 77.5◦ are not considered. Therefore, our new model takes into account the location and elevation angle to make it more applicable. Hence an extension for improving the performance assessment and analysis of satellite/Earth stations is achieved. Of all studied models, the Brazil, ITU-R-618-11, and DAH models gave the lowest root mean square (RMS) error for the three chosen states in Malaysia for stationary scenario. For the mobile scenario (Malaysia-PMMS), enables a first-hand coarse estimation of and an analysis attenuation because it is much simpler to obtain attenuation due to rain and power arch supply PAs. The attenuation rustled from rain either rain or power arch supply were measured independently. The obtained output were statistically analyzed to calculate the total attenuation composite (PAs with rain) time series synthesizer. A parallel to that, attenuation resulted from power arch supply were compared with noise floor level. This comparison is useful to validate attenuation due to power arch supply measurement. Incorporating both phenomena to enable a more comprehensive study of relevant fade mitigation techniques (FMTs). The underlying analytical tool represents a first effort (to be validated by measurements) to dynamically model mobile satellite links operating higher than 10 GHz. In order to increase the quantitative and qualitative information database of the satellite signal performance under link impairments in tropical regions.